Desain Pembelajaran Humanistik Islam: Integrasi Nilai Kemanusiaan dan Spiritualitas - Khaisyah Nurhasanah; Vilsi Kholillah; Gusmaneli (Journal of Religion and Social Community | E-ISSN : 3064-0326, 2025)
This study discusses the concept of Islamic humanistic instructional design as an educational approach that integrates humanistic values with Islamic teachings. This instructional design positions learners as the central subjects of the learning process and focuses on developing intellectual, emotional, social, and spiritual potentials in a balanced manner. The discussion includes the definition of instructional design, humanistic principles in Islamic perspective, the main characteristics of Islamic humanistic learning, and the implementation of humanistic learning theory in Islamic Religious Education (PAI). Its core principles include respect for human dignity, individual differences, self-reflection, and spiritual awareness with divine responsibility. The implementation in PAI emphasizes inclusive, reflective, and participatory learning, where teachers act as facilitators guiding students to deeply understand and practice Islamic values. Therefore, Islamic humanistic instructional design aims to form insan kamil a complete human being who is knowledgeable, virtuous, and responsible to oneself, others, and God.